Nrf2/HO-1 signaling pathway may be the prime target for chemoprevention of cisplatin-induced nephrotoxicity by lycopene - Şahin, Kazım; Tuzcu, Mehmet; Şahin, Nurhan; Ali, Shakir; Küçük, Ömer (Pergamon-Elsevier Science Ltd, 2010)
Cisplatin is used against various types of solid tumors. However, its use is limited by its nephrotoxicity, with about 25-35% patients experiencing a significant decline in renal function after a single dose of cisplatin. This study reports that lycopene mitigates the nephrotoxic effect of cisplatin in rat through Nrf2-mediated induction of heme oxygenase-1 (HO-1). Eight weeks old male rats (200-215 g) were supplemented with lycopene complex containing 6% lycopene, 1.5% tocopherols, 1% phytoene and phytofluene, and 0.2% beta-carotene for 10 days at a dose level of 6 mg/kg bw, followed by a single i.p. injection of cisplatin (7 mg/kg bw). Western blot analysis of renal Nrf2, HO-1 and NF-kappa B p65 showed that cisplatin-induced decrease in the levels of Nrf-2 and HO-1 was counteracted by lycopene. On the other hand, cisplatin mediated increase in NF-kappa B p65 was brought down by lycopene. Lycopene supplementation is reported to significantly improve the changes associated with cisplatin nephrotoxicity, as also evident by increased level of antioxidant enzymes. The study suggests that Nrf2/HO-1 signaling pathway may be the prime target for chemoprevention of cisplatin-induced nephrotoxicity by lycopene, and reduces inflammation by inhibiting NF-kappa B. Correlation between NF-kappa B and Nrf2 is discussed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cisplatin; Kidney; Nrf2; HO-1; Lycopene